2008
DOI: 10.3844/ajbbsp.2008.367.370
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Major Cultivable Aerobic Bacteria in the Oral Cavity of Malaysian Subjects

Abstract: Culture dependent and culture independent methods have shown that about 600 species of bacteria inhabit the human oral cavity. While some oral microorganisms have a direct link to dental caries, periodontal disease and halitosis, opportunistic pathogens may be responsible for systemic diseases such as bacterial endocarditis, aspiration pneumonia, osteomyelitis in children, preterm low birth weight, coronary heart disease and cerebral infarction (or stroke). This study employs bacterial 16S rDNA sequences to ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The frequent occurrence of Streptococcus sanguinis, Actinomyces viscosus, Neisseria subflava, and Lautropia sp. in supragingival plaque in the Thai subjects is broadly in agreement with a previous Malaysian study which similarly reported the presence of Streptococcus oralis, Streptococcus sanguinis, Actinomyces viscosus, Actinomyces naeslundii, Lautropia sp., Kingella oralis, Neisseria subflava, Neisseria mucosa, and Rothia mucilaginosa on the tooth surfaces of healthy persons (34 In the present study, Neisseria flavescens was detected only in dental plaque and not in the saliva of either nondiabetic or diabetic individuals. Neisseria, an obligate aerobe, has been implicated in the early stages of dental plaque development (48).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The frequent occurrence of Streptococcus sanguinis, Actinomyces viscosus, Neisseria subflava, and Lautropia sp. in supragingival plaque in the Thai subjects is broadly in agreement with a previous Malaysian study which similarly reported the presence of Streptococcus oralis, Streptococcus sanguinis, Actinomyces viscosus, Actinomyces naeslundii, Lautropia sp., Kingella oralis, Neisseria subflava, Neisseria mucosa, and Rothia mucilaginosa on the tooth surfaces of healthy persons (34 In the present study, Neisseria flavescens was detected only in dental plaque and not in the saliva of either nondiabetic or diabetic individuals. Neisseria, an obligate aerobe, has been implicated in the early stages of dental plaque development (48).…”
Section: Discussionmentioning
confidence: 61%
“…This approach has been previously used to profile the composition of oral microbial communities (17,34,35). DGGE analysis has been previously used in a limited number of studies to produce fingerprints of saliva (36,37) and supragingival plaque diversity (38,39), and some of these studies have combined DGGE, cluster analysis, and sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of force during orthodontic treatment will result in optimal tissue response and rapid tooth movement. Therefore orthodontic movement should be impressed with low forces (Berger, 2000), thus ensuring treatment efficiency in respect of biologic principles (Thorstenson and Kusy, 2003), oral flora (Koshy et al, 2008) arch forms (Mohammad et al, 2011) and allowing correct jaw movements (Zhuohua et al, 2010). Friction at the bracket archwire interface might prevent the attainment of optimal force levels in the supporting tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Many microorganisms including Staphylococcus species, Streptococcus species, and Lactobacillus species are found in human saliva (5) . Dental caries has been known to be caused by acidogenic and aciduric bacteria, such as mutans streptococci and lactobacilli (6,7) .…”
Section: Introductionmentioning
confidence: 99%